How do patients with exacerbated chronic obstructive pulmonary disease experience care in the intensive care unit?. Issue 4 (9th December 2013) - Torheim, Henny; Kvangarsnes, Marit
<x xml:space="preserve">Abstract</x> The aim was to gain insight into how patients with advanced chronic obstructive pulmonary disease (COPD) experience care in the acute phase. The study has a qualitative design with a phenomenological approach. The empirics consist of qualitative in‐depth interviews with ten patients admitted to the intensive care units in two Norwegian hospitals. The interviews were carried out from November 2009 to June 2011. The data have been analysed through meaning condensation, in accordance with Amadeo Giorgi's four‐step method. Kari Martinsen's phenomenological philosophy of nursing has inspired the study. An essential structure of the patients' experiences of care in the intensive care unit by acute COPD‐exacerbation may be described as: Feelings of being trapped in a life‐threatening situation in which the care system assumes control over their lives. This experience is conditioned not only by the medical treatment, but also by the entire interaction with the caregivers. The essence of the phenomenon is presented through three themes which describe the patient's lived experience: preserving the breath of life, vulnerable interactions and opportunities for better health. Acute COPD‐exacerbation is a traumatic experience and the patients become particularly vulnerable when they depend on others for breathing support. The phenomenological analysis shows that the patients experience good care during breath of life preservation when the care is performed in a way that gives patients more insight into their illness and gives new opportunities for the future.